(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
Background: Sexual differences in physiologies could results in significant variation in energy generation, allocation, and utilization among males and females organisms. Metabolic scaling exponents could as well be dimorphically varied in insects in which females are less active due to reproductive demands. This study investigated into the metabolic-mass scaling patterns of male and female American cockroach, Periplaneta americana. Methods: Metabolic rate was measured indirectly by estimating the rate of oxygen con sumption (VO2 ) and carbon dioxide evolution (VCO2 ) using manometric and titrimetric methods respectively. Least square regression was used to scale Log10 VO2 with Log10 Mass and inferential statistics of analysis of variance, t-test, and coefficient of determinant (R2) were used to test the goodness of regression slopes, compare slopes of regression lines, and test significance of the variance accounted for by each regression model, respectively, at p < 0.05. Results: The results show that the metabolic rate was significantly correlated with body mass for males (t24 = 67.8), females (t24 = 37.6), and both sexes combined (t49 = 22.4). Each regression model was also significant; males (F1, 48 = 69.7), females (F1, 48 = 261.4), and both sexes combined (F1, 98 = 88.9). The slopes of males and females lines were significantly dif ferent (t46 = 5.75); however, the slopes of regression lines of both sexes combined was not significantly different from that of males (t71 = 0.83). Conclusion: The results imply that there is a sexual difference in metabolic scaling expo nents of cockroaches since their regression models cannot be represented by a single line due to differences in their intercept.